Directorates of the Ministry of Agrarian Reform Iraq in 1958 - 1968 - حيدر حميد رشيد داليا محمد شهاب (College of Education for Women, 2019)
After the issuance of agrarian reform first law of 1958 events social economic accelerating out of sync with political events on the application of the agrarian reform law issued a government executive branch law number (74) in May 1959 was the introduction of the ministry of Agrarian reform and the development of a new system of the ministry of agrarian reform and its department to determine structural ministry the new work started department of the ministry ptt.